Animal welfare and sustainable animal production. (19th October 2016) - Orihuela, A.
Abstract : This paper describes the basic principles of animal behavior and how these concepts can be applied to the management and care of farm animal species in a sustainable way. Several examples about how the behavior of animals can be used to increase production and welfare understanding animal needs while solving farm problems, are mentioned. Topics covered include: fostering of orphans, explaining how to substitute dead lambs, or how to add extra lambs to ewes with single births; the breakdown of the cow–calf relationship, covering different forms of weaning, focusing on stress reduction as reproductive efficiency and productivity increases; handling system designs, explaining the basic principles of animal handling and how to leverage this knowledge in the design of facilities for the purpose of moving cattle efficiently, reducing at the same time the risk of injury in humans and animals; the behavior of sick animals, where the physiological processes in order to regain homeostasis through changes in animal behavior are explained, in addition to how those changes in behavior can be used to predict some diseases even before clinical signs appeared, or how these changes might be applied to assess the extent of the pain suffered by a particular individual; and finally, a miscellaneous section covering various behavioral aspects of management of productive animals.